Knowledge transfer: How do high performance coaches access the knowledge of sport scientists? - Reade, I.; Rodgers, W.; Hall, N. (International Journal of Sports Science and Coaching, 2008)
The purpose of this research was to answer three specific questions: i) How do coaches perceive sport science research? ii) What sources do coaches consult when looking for new ideas? and iii) What barriers do coaches encounter when trying to access new information? All of the high-performance coaches involved in Canadian Interuniversity Sport (CIS) were contacted to complete an on-line survey related to these questions. There were 205 coaches who completed at least part of the questionnaire. There was a strong consensus that the CIS coaches believe that sport science makes an important contribution to high-performance sport. Gaps exist between what coaches are looking for and the research that is being conducted, especially in the area of tactics and strategies. Coaches are most likely to consult other coaches, or attend coaching conferences to get new information. Sport scientists and their publications were ranked very low by the coaches as a likely source of sport science information. The barriers to the coaches' access to sport science are the time required to find and read scientific journals, and lack of direct access to a sport scientist. Strategies to remove the barriers could include rewarding sport scientists for successful transfer of their knowledge to practice through direct communication with coaches.